Toward a Transformation of Practices in Teacher Education - Lenoir, Yves (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2011)
This article underscores the need for a profound transformation in the training processes of future teachers, and thereby in teaching practices. The text first presents various grounds for this transformation, citing social, economic-political, teleological, axiological, epistemological, and psychological factors. It then focuses on teacher development practices that need to change, highlighting the modifications to be brought to educational objectives, and in particular underscoring the essential need for a new approach in terms of relationships to knowledge and to students and other teacher educators. Finally, the article offers approaches for change in teacher education. In so doing, it argues for the establishment of appropriate conditions, the piloting of change, and for changes in the context of training and evaluation processes.